2021
DOI: 10.1097/gme.0000000000001835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free androgen index on blood pressure variability and target organ damage in postmenopausal hypertensive women: findings from a cross-sectional study

Abstract: Objective: The present study investigated the effects of free androgen index (FAI) on ambulatory blood pressure (ABP) and target organ function in postmenopausal hypertensive women. Methods: A total of 285 postmenopausal hypertensive women (mean age 54.06 ± 3.61) were admitted to the Department of Hypertension of Lanzhou University Second Hospital between December 2018 and December 2020. According to the serum FAI level, the participants were divided into a low-FAI (<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Zhang et al found that FAI and free testosterone (FT) were significant factors associated with fertility outcomes in infertile PCOS patients, with FAI showing a significant correlation with ovulations per cycle, clinical pregnancy, hCG positive, and live birth rates. When FAI exceeded 7.85, the pregnancy rate and live birth rate significantly decreased, while the conception rate increased inversely [ 15 , 27 ], FAI may serve as a significant predictor for conception, pregnancy, and LBR [ 28 , 29 ]. Additionally, Kuang et al demonstrated that combining FAI with factors such as age and insulin levels could predict at least one pregnancy outcome [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that FAI and free testosterone (FT) were significant factors associated with fertility outcomes in infertile PCOS patients, with FAI showing a significant correlation with ovulations per cycle, clinical pregnancy, hCG positive, and live birth rates. When FAI exceeded 7.85, the pregnancy rate and live birth rate significantly decreased, while the conception rate increased inversely [ 15 , 27 ], FAI may serve as a significant predictor for conception, pregnancy, and LBR [ 28 , 29 ]. Additionally, Kuang et al demonstrated that combining FAI with factors such as age and insulin levels could predict at least one pregnancy outcome [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%